1991
DOI: 10.1177/036354659101900411
|View full text |Cite
|
Sign up to set email alerts
|

An experimental evaluation of isometric placement for extraarticular reconstructions of the anterior cruciate ligament

Abstract: We measured the changes in distance between the tibial and femoral attachment points of the extraarticular ACL substitute during knee motion. To measure the changes in distance continuously and directly, a computer-assisted experimental system was developed using an electrolyte-in-rubber transducer. We used 6 cadaveric knees to measure changes in distance of 15 combinations during a simple flexion and extension knee motion. The distance became longer with flexion in each pair of attachment locations. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 16 publications
1
19
0
1
Order By: Relevance
“…Only a few studies of the isometry of lateral extra-articular reconstructions have been published, with none of these considering a graft passing deep to the LCL. 10,22,23,41 Given that a lateral reconstruction is intended to stabilize the weightbearing knee and that the knee has greater rotational laxity when flexed, it may be desirable for a graft to be longer/tighter in extension and shorter/slacker in flexion.…”
mentioning
confidence: 99%
“…Only a few studies of the isometry of lateral extra-articular reconstructions have been published, with none of these considering a graft passing deep to the LCL. 10,22,23,41 Given that a lateral reconstruction is intended to stabilize the weightbearing knee and that the knee has greater rotational laxity when flexed, it may be desirable for a graft to be longer/tighter in extension and shorter/slacker in flexion.…”
mentioning
confidence: 99%
“…Its free end was prepared with Krakow sutures using Ethibond 2 (Ethicon, Somerville, NJ, USA). For the femoral fixation, an 8mm diameter tunnel was drilled at the most isometric femoral point described by Kurosawa et al 16 for ACL extra-articular reconstruction. The graft was routed deeply to the lateral collateral ligament (LCL) according to the Cooker-Arnold technique.…”
Section: Case Reportmentioning
confidence: 99%
“…The graft was routed deeply to the lateral collateral ligament (LCL) according to the Cooker-Arnold technique. 16 An interference screw BIORCI HA 8mm x 35mm (Smith & Nephew, Inc, Andover, MA, USA) was used to fix the graft with the knee at 45º of flexion in neutral rotational. During the stability evaluation tests, it was noticed a graft rupture at the femoral tunnel aperture.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers who agree with the standards indicated by our results for these fiber bundles are Crowninshield et al 7 and Shelburne & Pandy, 27 although the latter reported a slight slackening of the fibers in the 30°-to-60° angular moment, and Fox et al 28 and Li et al 23 found a maximum tension of the bundle at 90°. On the other hand Kurosawa et al 29,30 described a slackening of the fibers in the most posterior positions, while Beynnon et al 22 reported a slackening of the fibers as a unit during knee flexion, and Amis et al 31 reported that the posterolateral and posteromedial structures tighten as the knee extends. Harner et al 32,33 indicated that this bundle plays an important role in joint stabilization after PCL reconstruction.…”
Section: Medial Bundlementioning
confidence: 99%